Tezepelumab Efficacy in Patients with Severe, Uncontrolled Asthma with Comorbid Nasal Polyps in NAVIGATOR [Corrigendum] - Laidlaw TM; Menzies-Gow A; Caveney S; Han JK; Martin N; Israel E; Lee JK; Llanos JP; Martin N; Megally A; Parikh B; Vong S; et al. (Journal of Asthma and Allergy, 2023)
Laidlaw TM, Menzies-Gow A, Caveney S, et al. J Asthma Allergy. 2023;16:915–932. The authors have advised there is an error in Figure 1 on page 922. The n= x-axis data were transposed for the treatment groups for both the Patients with NPs and Patients without NPs. The correct Figure 1 is as follows.